Role of improved seed on agricultural transformation in Cambodia - Sarom, Men (International Food Policy Research Institute, 2014)
Due to internal conflicts and civil war, the green revolution largely passed by Cambodia without having a significant effect on rice production. With an estimated population of 14.7 million, 80 percent of which are rural and most dependent on agriculture as their main source of income, rice productivity is of critical importance in a country where more than 30 percent of the population still lives below the national poverty line. The lift of the economic embargo on Cambodia in 1993 opened the country up to greater integration with the sub-regional, regional and global cooperation networks and has led to significant agricultural and economic progress. In addition, peace allowed for an expansion of cultivation area from 1.9 million hectares in 1990 to 3 million hectares today.